Single nucleotide polymorphisms as the new predictors of therapy decisions in gastroesophageal junction and gastric adenocarcinoma? - Perkhofer, Lukas; Hann, Alexander (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Western populations show a remarkable switch in gastroesophageal cancer phenotype with predominance for adenocarcinomas nowadays (1). This contrasts the rest of the world and is mainly caused by lifestyle factors (2). Thereby, obesity and gastroesophageal reflux with Barret’s esophagus are the suspected correlates (3,4). Primary diagnosis of gastroesophageal junction (GEC)/gastric cancer (GC) with potentially curatively resectable disease stage is not uncommon (5).